A Study on the Dynamic Performance for Hydraulically Damped Rubber Bushings with Multiple Inertia Tracks and Orifices: Parameter Identification and Modeling - Chao-Feng Yang; Zhi-Hong Yin; Wen-Bin Shangguan; Xiao-Cheng Duan (Shock and Vibration)
Hydraulically damped rubber bushings (HDBs) are important for vehicle noise, vibration, and harshness (NVH) performance as they are able to decay the vehicle’s oscillation induced by engine and road. The dynamic stiffness and loss angle of an HDB are crucial and it is significant to investigate the relations between the design parameters with the dynamic stiffness and loss angle. Therefore, the force-deflection relation of the HDB is measured statically and the dynamic stiffness and loss angle are measured dynamically and the test data are analyzed with a view to examine how the measurement results are influenced by the design parameters (the number of the fluid tracks). Compared with the results predicted by a nonlinear lumped parameter model whose parameters are extracted by a parameter identification technique, using the model, the effect of the main rubber and the fluid track on the dynamic stiffness and the loss angle is investigated. A unified analytical model of HDB is also developed with the purpose of predicting the static and dynamic characteristics, and the predictions are shown to be well correlated with the measurement data. The good correlation suggests the validity of the model and the parameter identification implementation.